New dynamics of e-commerce on the retail industry: Analysis of the purchase process of fashion and electronics products - Gonçalves, R.; Dias, C.; Pereira, L.; Lopes da Costa, R.; Dias, Á.; Vinhas da Silva, R. (International Journal of Economics and Business Research, 2024)
The technology-mediated environment promoted the creation of new dynamics in the retail sector. To understand how the emergence of e-commerce has impacted the retail sector, this study analysed two distinct product typologies: fashion and electronics. Among the various conclusions of this work, we highlight a clear resistance to the emergence of e-commerce, even though a considerable part of the sample declares that the frequency of visits to physical stores has decreased, and the total frequency of purchases has increased after the appearance of e-commerce. The probability of completion of the purchase occurring on either platform increases when the search for information occurs on the same platform, however, possibly justified by the level of complexity of the product, the probability of the customer staying on the same platform during the electronics purchase process is marginally inferior to the fashion product model.